MAIN RISKS IN THE LITHUANIAN BANKING SECTOR: ANALYSIS AND EVALUATION - Jasevičienė, Filomena; Valiulienė, Vaida (Ekonomika, 2013)
Abstract. There are a number of different financial market institutions such as banks, credit unions, leasing and insurance companies, as well as capital market players in Lithuania. The bank sector makes the largest part of the financial market (more than 80%). Thus, the bank sector has a considerable influence on the country’s economy. Banks are not specialized in Lithuania, i.e. they are universal banks which seek to provide quite a wide range of financial services. The successful performance of a bank mostly depends on how it succeeds to manage the risks. The problems of risk management are becoming an object of exceptional attention while enhancing the variety of analysed risks as well as developing the investigation instruments both in the whole world and in Lithuania. Loans make the largest part of bank assets. So, the loan risk management is one of the most important guarantees of safe banking. To manage effectively the bank credit risk, it should be adequately evaluated.Key words: banks, credit risk, credit risk management, credit quality, non-performing loansp>